Industry-Based Curriculum Development Management in Improving Student’s Competence - Supriadi Adung; Akhmad Sanusi; Didin Wahidin; Heru Sujianto (Journal of Islamicate Studies, 2021)
The problem of developing a special curriculum for vocational high schools has become a central issue in the implementation of curriculum diversification that is oriented towards the industrial world, so it is deemed necessary to examine its implementation in vocational education units (SMK). For this reason, this study aims to describe fisheries: planning, organizing, implementing; and Supervision / evaluation of industry-based curriculum development management in improving the competence of vocational students. This research uses a qualitative approach with descriptive methods. Data collection techniques through in-depth interviews, observation and documentation. Data were analyzed using interactive analysis techniques consisting of data collection, data reduction, data presentation, and conclusions. The results showed that: (1), Industry-based curriculum development management planning in improving the competence of students at the two SMKs in Bandung Regency through: Preparation stage: formulating objectives, and context analysis (SWOT); Validation stage through the determination of programs and strategic plans, as well as recommendations, the implementation stage and committee considerations; and the Verification Stage. (2) the organization is formed from: elements of the school, school committee, elements of the world of business / industry and elements of government); (3) Implementation is carried out through the management of: Implementative Curriculum; Student competency development; Implementation of teaching and learning activities and assessment of learning outcomes. (4) Monitoring / evaluation through: (a) Monitoring learning methods and student achievement (assessment of learning outcomes). (b) Academic Supervision; (c) The number and quality of the ability of graduates; and (d) internal audit. Other findings in this study are the impact of industry-based curriculum development management, constraints and efforts to overcome them.